Pre-breeding efforts through introgression of pre-harvest sprouting resistance genes from wild Vigna radiata var. sublobata into cultivated mungbean - Patil, Deepak Khanderao; Dhare, Sachin Laxman; Gite, Vishnu Kishanrao; Kalpande, Hirakant Vishwasrao; Thakur, Niranjan Ravindra; Pratap, Aditya; Baig, Khizer Samad; Ahire, Rakesh Dnyandeo (Frontiers in Plant Science, 2025)
IntroductionPre-harvest sprouting (PHS), triggered by heavy, prolonged rainfall and high humidity during the pod ripening stage, is a significant constraint on mungbean production, causing severe losses in yield and quality. This results in poor seed quality and a reduced market value.MethodsThis study, conducted at the Agriculture Research Station, Badnapur, Maharashtra, aimed to develop PHS-resistant mungbean lines through introgression of resistance genes from the wild species, Vigna radiata var. sublobata. Seven PHS-tolerant inter-specific derivatives were identified from a cross between the elite cultivar BM-4 and the wild accession BWM-29. These derivatives were further crossed with six locally adapted varieties from different agroclimatic regions, producing 42 cross combinations. Parental lines and their crosses were evaluated for PHS incidence and fresh seed germination (FSG) under control conditions.Results and discussionWide genetic variation was observed, for PHS ranging from 3.55% to 98.86% and FSG from 4.76% to 96.17%. Four crosses exhibited less than 10% PHS, indicating strong tolerance. Correlation analysis revealed a significant positive correlation between the FSG and PHS. Genetic analysis indicated that PHS is controlled by a single gene, with dormancy dominant over non-dormant, representing the major finding of this research. Principal component analysis revealed that PHS and FSG were the main contributors to the observed variability. Based on PHS tolerance, crosses were categorized as tolerant, moderately tolerant, moderately susceptible, and susceptible groups. The identified PHS-tolerant crosses and male parents will be valuable resources for mungbean breeding. This study highlights the importance of utilizing wild genetic resources and inter-specific hybridization to enhance PHS tolerance in the mungbean providing a robust foundation for breeding resilient, high yielding climate-adapted cultivars.